THE EFFECT OF SUSTAINABILITY DISCLOSURE, CORPORATE GOVERNANCE MECHANISM AND INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE - Nita Yuliana; Wiwik Utami (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2022)
This study examines the effect of sustainability disclosure, corporate governance mechanisms, and Intellectual capital on financial performance. The research population of this study are banking companies listed on the IDX 2016-2019. The sample selected based on the criteria are 27 companies with 4 years of period, then 108 samples are obtained. Regression analysis method on panel data. The results of the study show that the disclosure of sustainability and institutional ownership has a negative effect on financial performance. The frequency of board of Commissioners meetings and Intellectual capital have a positive and significant effect on financial performance.